Evaluating the association of depressive symptoms on serum folate and erythrocyte folate levels based on the 2017–2020 NHANES database - Yang, Yunhong; Qi, Huaqian; Zhang, Jiahao; Jia, Jie; Yang, Yunsong; Zhao, Hong (Frontiers in Nutrition, 2025)
ObjectiveTo improve further the management of the nutritional status and dietary habits of depressed patients.MethodsThis study investigated the effect of different severity states of depressive symptoms on serum and erythrocyte folate levels using the Nutrition Examination Survey (NHANES) database from 2017 to 2020. We comprised a sample of 4,872 cases from NHANES database. We developed 3 linear regression models to assess the effect of depressive symptoms on erythrocyte folate and serum folate by collating and analyzing the data. The relationship between depression severity and erythrocyte folate as well as serum folate was also mutually validated by the results of multiple logistic regression. Finally, we made restricted cubic spline plots using the glm function of R.ResultsDepression remained negatively correlated with serum folate levels with a OR value of −0.02, 95% CI of −0.05 ~ −0.00. Moderate depression was negatively correlated with folate, with a OR value of −0.03, 95% CI of −0.05 ~ −0.00. When exploring the association between different degrees of depressive symptoms and erythrocyte folate, it was unexpectedly found that major depression was negatively associated with erythrocyte folate with a OR value of −0.18, 95% CI of −0.31 ~ −0.04 after adjusting for all covariates.ConclusionDepression is associated with folate levels. The risk of serum folate insufficiency or erythrocyte folate insufficiency is higher after a positive depression. For different degrees of depressive symptoms, serum folate levels were significantly lower than normal in patients with moderate depression, while erythrocyte folate levels were lower than normal in patients with major depression. Therefore, attention should be paid to the dietary habits and nutritional status of patients with depression or depressive symptoms when they are undergoing long-term antidepressant treatment. Folic acid supplementation is recommended for patients with moderate or severe depression or for depressed patients who have developed unhealthy eating habits.